Study of Biological Activities and ADMET-Related Properties of Novel Chlorinated N-arylcinnamamides - Strharsky, Tomas; Pindjakova, Dominika; Kos, Jiri; Vrablova, Lucia; Michnova, Hana; Hosek, Jan; Strakova, Nicol; Lelakova, Veronika; Leva, Lenka; Kavanova, Lenka; Oravec, Michal; Cizek, Alois; et al. (International journal of molecular sciences, 2022)
A series of eighteen 4-chlorocinnamanilides and eighteen 3,4-dichlorocinnamanilides were designed, prepared and characterized. All compounds were evaluated for their activity against gram-positive bacteria and against two mycobacterial strains. Viability on both cancer and primary mammalian cell lines was also assessed. The lipophilicity of the compounds was experimentally determined and correlated together with other physicochemical properties of the prepared derivatives with biological activity. 3,4-Dichlorocinnamanilides showed a broader spectrum of action and higher antibacterial efficacy than 4-chlorocinnamanilides; however, all compounds were more effective or comparable to clinically used drugs (ampicillin, isoniazid, rifampicin). Of the thirty-six compounds, six derivatives showed submicromolar activity against Staphylococcus aureus and clinical isolates of methicillin-resistant S. aureus (MRSA). (2E)-N-[3,5-bis(trifluoromethyl)phenyl]- 3-(4-chlorophenyl)prop-2-enamide was the most potent in series 1. (2E)-N-[3,5-bis(Trifluoromethyl)phenyl]-3-(3,4-dichlorophenyl)prop-2-enamide, (2E)-3-(3,4-dichlorophenyl)-N-[3-(trifluoromethyl)phenyl]prop-2-enamide, (2E)-3-(3,4-dichloro- phenyl)-N-[4-(trifluoromethyl)phenyl]prop-2-enamide and (2E)-3-(3,4-dichlorophenyl)- N-[4-(trifluoromethoxy)phenyl]prop-2-enamide were the most active in series 2 and in addition to activity against S. aureus and MRSA were highly active against Enterococcus faecalis and vancomycin-resistant E. faecalis isolates and against fast-growing Mycobacterium smegmatis and against slow-growing M. marinum, M. tuberculosis non-hazardous test models. In addition, the last three compounds of the above-mentioned showed insignificant cytotoxicity to primary porcine monocyte-derived macrophages.
Keywords: prasata; Swine; stafylokokové infekce; Mammals; Staphylococcus aureus; antibakteriální látky; antimicrobial activity; Microbial Sensitivity Tests; ampicilin; lipophilicity; savci; cinnamamides; Animals; cytotoxicity; Methicillin-Resistant Staphylococcus aureus; Anti-Bacterial Agents; zvířata; mikrobiální testy citlivosti; Staphylococcal Infections; structure-activity relationships; Ampicillin; methicilin rezistentní Staphylococcus aureus; Mycobacterium tuberculosis